Sutural deformation during bone-anchored maxillary protraction - Vracar, Taylor Rae (J Oral Biol Craniofac Res, 2021)
INTRODUCTION: Bone-anchored maxillary protraction (BAMP) is an emerging treatment option for orthopedic correction of maxillary deficiency in young patients. Compared to reverse pull headgear (RPHG), it is believed that forces generated during BAMP result in greater circum-maxillary sutural separation, mandibular retrusion, and improved maxillary protraction. Mechanical loading of the circum-maxillary sutures during BAMP is still poorly understood. METHODS: 20 ex-vivo pig heads were used. Miniplates and molar tubes were installed like clinical procedures. A series of five 200 ​g-force (gf) elastics were applied on the right and left side until 1000gf were reached. Strain gauges were installed across the zygomatico-maxillary (ZMS), zygomatico-temporal (ZTS), and nasofrontal suture (NFS). Differential variable reluctance transducers (DVRTs) were installed across the ZTS. Deformation of the sutures during BAMP and RPHG was measured and compared. RESULTS: Higher average sutural deformation of the ZTS and ZMS was seen in BAMP than RPHG: 36.6 ​± ​20.6με vs 18.0 ​± ​12.4με and 54.7 ​± ​28.5με vs 12.5 ​± ​14.8με, respectively. Similarly, higher NFS deformation was seen in BAMP (18.4 ​± ​12.9με vs. −0.8 ​± ​12.0με). DVRT data showed higher ZTS separation in BAMP than RPHG (6.3 ​± ​5.2 ​μm vs. 1.7 ​± ​2.1 ​μm). These differences were all statistically significant using the Wilcoxon-signed rank test. CONCLUSION: Both RPHG and BAMP forces separate the ZTS and ZMS. BAMP resulted in higher levels of sutural separation at the ZTS and ZMS by 2- and 5-fold, respectively.